The effect of transcranial direct current stimulation (tDCS) on food craving, reward and appetite in a healthy population. (1st February 2021) - Beaumont, Jordan D.; Davis, Danielle; Dalton, Michelle; Nowicky, Alexander; Russell, Mark; Barwood, Martin J.
Abstract: The ability to control hedonic appetite is associated with executive functioning, originating in the prefrontal cortex (PFC). These rewarding components of food can override homeostatic mechanisms, potentiating obesogenic behaviours. Indeed, those susceptible to overconsumption appear to have PFC hypo-activation. Transcranial direct current stimulation (tDCS) over the dorsolateral PFC (DLPFC) has been shown to reduce food craving and consumption, potentially via attenuating this reward response. We examined the effects of stimulation on food reward and craving using a healthy-weight cohort. This study is amongst the first to explore the effects of tDCS on explicit and implicit components of reward for different food categories. Twenty-one healthy-weight participants (24 ± 7 years, 22.8 ± 2.3 kg m −2 ) completed two sessions involving double-blind, randomised and counterbalanced anodal or sham tDCS over the right DLPFC, at 2 mA for 20 min. Food craving (Food Craving Questionnaire-State), reward (Leeds Food Preference Questionnaire), and subjective appetite (100 mm visual analogue scales) were measured pre- and post-tDCS. Eating behaviour trait susceptibility was assessed using the Three Factor Eating Questionnaire-Short Form, Control of Eating Questionnaire, and Food Craving Questionnaire-Trait-reduced. Stimulation did not alter food craving, reward or appetite in healthy-weight participants who displayed low susceptibility to overconsumption, with low trait craving, good craving control, and low uncontrolled eating and emotional eating behaviour. Implicit and explicit reward were reliable measures of hedonic appetite, suggesting these are robust targets for future tDCS research. These findings suggest that applying tDCS over the DLPFC does not change food reward response in individuals not at risk for overconsumption, and future work should focus on those at risk of overconsumption who may be more responsive to the effects of tDCS on hedonic appetite. Highlights: We consider the effects of tDCS on implicit and explicit reward using a validated task. High reliability in reward measures suggest a robust target for future tDCS studies. Previously findings are limited by high variation within food-related variables. Effects of tDCS may be dependent on participant eating behaviour traits. Future work should screen participants using validated psychometric questionnaires.